Prediction of protein contacts from correlated sequence substitutions. (28th March 2013) - Sadowski, Michael; Taylor, William
Recent work has led to a substantial improvement in the accuracy of predictions of contacts between amino acids using evolutionary information derived from multiple sequence alignments. Where large numbers of diverse sequence relatives are available and can be aligned to the sequence of a protein of unknown structure, it is now possible to generate high-resolution models without recourse to the structure of a template. In this review, we describe these exciting new techniques and critically assess the state of the art in contact prediction in light of them. We discuss areas for immediate research and development as well as potential future developments.